Phase I Study of Safety, Tolerability, and Efficacy of Tebentafusp Using a Step-Up Dosing Regimen and Expansion in Patients With Metastatic Uveal Melanoma. Issue 17 (10th June 2022) - Carvajal, Richard D.; Nathan, Paul; Sacco, Joseph J.; Orloff, Marlana; Hernandez-Aya, Leonel F.; Yang, Jessica; Luke, Jason J.; Butler, Marcus O.; Stanhope, Sarah; Collins, Laura; McAlpine, Cheryl; Holland, Chris; et al.
Abstract : PURPOSE: This phase I study aimed to define the recommended phase II dose (RP2D) of tebentafusp, a first-in-class T-cell receptor/anti-CD3 bispecific protein, using a three-week step-up dosing regimen, and to assess its safety, pharmacokinetics, pharmacodynamics, and preliminary clinical activity in patients with metastatic uveal melanoma (mUM). METHODS: In this open-label, international, phase I/II study, HLA-A*02 or HLA-A*02:01+ patients with mUM received tebentafusp 20 μg once in week 1 and 30 μg once in week 2. Dose escalation (starting at 54 μg) began at week 3 in a standard 3 + 3 design to define RP2D. Expansion-phase patients were treated at the RP2D (20-30-68 μg). Blood and tumor samples were collected for pharmacokinetics/pharmacodynamics assessment, and treatment efficacy was evaluated for all patients with baseline efficacy data as of December 2017. RESULTS: Between March 2016 and December 2017, 42 eligible patients who failed a median of two previous treatments were enrolled: 19 in the dose escalation cohort and 23 in an initial dose expansion cohort. Of the dose levels investigated, 68 μg was identified as the RP2D. Most frequent treatment-emergent adverse events regardless of attribution were pyrexia (91%), rash (83%), pruritus (83%), nausea (74%), fatigue (71%), and chills (69%). Toxicity attenuated following the first three doses. The overall response rate was 11.9% (95% CI, 4.0 to 25.6). With a median follow-up of 32.4 months, median overall survival was 25.5 months (range, 0.89-31.1 months) and 1-year overall survival rate was 67%. Treatment was associated with increased tumor T-cell infiltration and transient increases in serum inflammatory mediators. CONCLUSION: Using a step-up dosing regimen of tebentafusp allowed a 36% increase in the RP2D compared with weekly fixed dosing, with a manageable side-effect profile and a signal of efficacy in mUM.